PERSONALITY AND COGNITIVE FACTORS IN INFORMATION SYSTEM MIGRATION PROCESS - Abdillah, Willy (Journal of Indonesian Economy and Business, 2013)
This study predict potential resistance of IT adoption from perspective of cognitive andpersonality. Research conducted on 30 employees of PT. Berau Coal and 54 employees ofPDAM Boyolali who are undergoing the process of migration of ERP and e-billing. Nonprobabilitysampling procedure was using in this research with purposive-judgmenttechniques. Primary data retrieved through a questionnaire with a closed question format.Hypothesis testing conducted using Partial Least Square with software applications2.0.M3 version SmartPLS.The results show only the cognitive factors have positively influence on intention toadopt ERP and e-billing. This finding reinforces that the development of IT adoptiontheory will lead to perceptual factors. Also, this finding indicates that the employees of PT.Beraucoal and PDAM Boyolali have great intentions to use IT in term of ERP and ebillingmigration process. Managerial implication and further researches are discussed.Keywords: Personality Factors, Cognitive Factors, Information Technology Acceptance,ERP and e-billing.